2012
DOI: 10.5402/2012/839612
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis and Properties of Novel Bi2Se3 Nanostructures and Microplatelets

Abstract: Bi 2 Se 3 nanostructures, microsised fibre bundles, and platelets have been synthesised through a simple chemical spray pyrolysis route on glass substrates. Low substrate temperatures (T sub ) favoured growth of nanostructures while elevated T sub was accompanied by increased grain growth and formation of microsised platelets. The nanostructures were identified as nanorods, nanofibers, nanotubes, nanoflowers, and nanoneedles of various aspect ratios. There was an observed red shift of the optical band gap (E o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Bi 2 Se3 Thin films have been prepared using various techniques such electro deposition [12] and Successive Ionic Layer Absorption and Reaction (SILAR) 13] methods] .The structure of Bi 2 Se 3 thin films were studied [14][15][16][17][18][19][20], It was found that, these films had polycrystalline structure with rhombohedral structure of Bi 2 Se 3 [17][18], space group (R¯3m) (166) [20]. Optical properties of Bi2Se3 thin films were studied [21][22][23][24][25][26][27], It was found that, the energy gap was 1.51 [21], with range 1.4 -2.25 eV [22], 1.10 eV and decrease with annealing [23],1.25 eV decrease with substrate temperature [24], 1.22 eV decreased wit temperature [25]. the transmitted values increased with annealing [26], The Bi2Se3 thin films had a direct transitions [27].…”
Section: Introductionmentioning
confidence: 99%
“…Bi 2 Se3 Thin films have been prepared using various techniques such electro deposition [12] and Successive Ionic Layer Absorption and Reaction (SILAR) 13] methods] .The structure of Bi 2 Se 3 thin films were studied [14][15][16][17][18][19][20], It was found that, these films had polycrystalline structure with rhombohedral structure of Bi 2 Se 3 [17][18], space group (R¯3m) (166) [20]. Optical properties of Bi2Se3 thin films were studied [21][22][23][24][25][26][27], It was found that, the energy gap was 1.51 [21], with range 1.4 -2.25 eV [22], 1.10 eV and decrease with annealing [23],1.25 eV decrease with substrate temperature [24], 1.22 eV decreased wit temperature [25]. the transmitted values increased with annealing [26], The Bi2Se3 thin films had a direct transitions [27].…”
Section: Introductionmentioning
confidence: 99%